EDUKASI PENGELOLAAN LINGKUNGAN HIDUP BERBASIS EKOSISTEM UNTUK ANAK SDN 119 BELALANG - Sarmila Sarmila; Muliana Muliana; Erwing Erwing (LPPM Institut Pendidikan Nusantara Global, 2025)
The ecosystem-based environmental management education program was implemented at SDN 119 Belalang to raise students' awareness of the importance of protecting the environment. This program teaches students about ecosystems and encourages them to understand the relationship between human activities and their environmental impact through interactive activities such as planting trees, managing waste, and observing flora and fauna. The qualitative methodology used in this service involves in-depth interviews, classroom observations, and group discussions with students, focusing on collecting descriptive data. Research findings show that such educational programs are effective in increasing awareness of sustainable natural resource management and ecosystem balance. However, challenges such as limited resources and the need for educator training must be addressed. To address these, collaboration between schools, environmental organizations, and local communities is crucial for the success of this program. Overall, this ecosystem-based education program helps children become active change agents, fostering attitudes that can support long-term environmental sustainability. If implemented properly, this approach can contribute to global efforts to address complex environmental challenges and ensure a balanced and sustainable environment for future generations.